Data from air, englacial and permafrost temperature measurements on Mt. Ortles (Eastern European Alps) ... - Carturan, Luca; De Blasi, Fabrizio; Dinale, Roberto; Dragà, Gianfranco; Gabrielli, Paolo; Mair, Volkmar; Seppi, Roberto; Tonidandel, David; Zanoner, Thomas; Zendrini, Tiziana Lazzarina; Dalla Fontana, Giancarlo (Zenodo, 2023)
The *.csv files report the temperature data recorded between 2010 and 2016 and presented in the paper “Modern air, englacial and permafrost temperatures at high altitude on Mt. Ortles, (3905 m a.s.l.) in the Eastern European Alps” (Carturan et al., 2023, submitted). The data were used to display the time series reported in the paper, which details variable names, data quality flags, maintenance logs of field operations, and characteristics of measurement sites. The data files contain measurements of air temperature, englacial temperature, soil surface temperature and rockwall temperature. The file named ‘Ortles_Temperature_Metadata.pdf’ contains information regarding variable names, structure of data files, quality codes, geolocation, and topographic and geomorphological characteristics of sites instrumented for temperature measurements. Reference: Carturan, L., De Blasi, F., Dinale, R., Dragà, G., Gabrielli, P., Mair, V., Seppi, R., Tonidandel, D., Zanoner, T., Zendrini, T. L., and Dalla Fontana, G.: Modern ... : This dataset was collected in the framework of the Ortles Project (a program supported by two NSF awards no. 1060115 & no. 1461422 to The Ohio State University and by the Ripartizione Protezione Antincendi e Civile of the Autonomous province of Bolzano in collaboration with the Ripartizione Opere idrauliche e Ripartizione Foreste of the Autonomous province of Bolzano and the Stelvio National Park) and of the Italian MIUR Project (PRIN 2010-11), "Response of morphoclimatic system dynamics to global changes and related geomorphological hazards" (local and national coordinators G. Dalla Fontana and C. Baroni). ...